CoMMoN: The Real-Time Container and Migration Monitoring as a Service in the Cloud - Dawadi, Babu Ram; Shakya, Subarna; Paudyal, Rajendra (Journal of the Institute of Engineering, 2017)
With the advancement of computing technologies, the modern cloud computing and virtualization system is highly distributed by the invention of better and light weight distributed applications packaging toolkit over the cloud environment, called the container technology. Cloud containers feature the management of applications with easy plug and play ability, migration, replication, relocation, upgrading et cetera in the real time. Such containers running different applications over the cloud infrastructure may consume different resources that require real time monitoring. Docker is an open source platform independent tool to create, deploy, and run applications by using Containers. Billions of applications for the end users and SMEs running over the cloud require efficient management, monitoring and operations to achieve better SLAs for cloud service providers. With this research, a Docker Container and Migration Monitoring System (CoMMoN) has been developed in which a customer running its application in a Container shall monitor its application in the real-time as well as take decision for the migration of Container to another network by service provider for liad balancing or by the customer under the violation of SLA. Once the customer registers its Container to the monitoring system, the monitoring probe collects different monitoring metrics and sends those parameters to remote monitoring system. The system which stores the monitoring metrics into InFluxDB, a time series database, also monitors the real-time migration of the Containers among the network. Journal of the Institute of Engineering, 2016, 12(1): 51-62